Secagem de gelatina : análise do perfil de concentração e temperatura no interior do gel - Silva, Edson Antonio da (1995)
This work has the objective of obtaining a numerical simulation of the process of gelatin drying. The simulation was conducted by coupling the drying of the bed with the drying of its cylindrical particles. Mass, momentum and energy balances were applied for the whole bed and its particles, obtaining thus, the drying model of a fixed bed packed with cylindrical particles of gelatin subject to a batch drying .The resulting differential equations of this model were written in function of bed depth and time. The variable bed depth was discretized producing a system of ordinary differential equations that was solved by the method of Gear. The solution of the particle equations was obtained with the boundary elements method, which has shown high precision even in the cases where high gradients of humidity appear inside the gelatin. During the initial drying phase the mechanism that controls drying is the diffusion of water vapour, formed on the surface of the gelatin, up to the main stream. After the end of this phase there are two mechanisms which influence drying. The first is the diffusion of water inside the gel up to its surface where evaporation occurs, and the second is the diffusion of water vapour up to the main stream .The gelatin used in the drying experiments had cylindrical geometry with the followings average dimensions: diameter 0,3 cm and height 5,0 cm. The good performance of the deveioped nuinericai modei was evidenced by good agreement with the experimentais resuits avaiiabie on drying at different conditions of air feed.